Investigation and experiment of radar system in unmanned aerial vehicles-I - Lin, David Chengwei (2015)
As technology advances, Unmanned Aerial Vehicles (“UAV”) are globally used for commercial or military. The common usage between these two are to capture image from above. In commercial world, cameras are directly mounted onto the UAV to capture videos or images remotely using a controller but cameras have distance limitation. In military, radar is being used for longer range imaging using a suitable modulation of waveform as the signal and transmitted via antennas. This paper will cover the modulation technique used for the radar system with high frequency supported with theoretical calculations of retrieving the beat signal.